A novel method of reactive voltage optimisation for photovoltaic systems. (21st April 2020) - Zhang, Wei Min; Zhang, Yan Xia
In this paper, a novel method is proposed for real-time adaptive reactive power optimisation of photovoltaic systems derived from the improved dynamic teaching and learning reactive power optimisation based on moth-flame optimisation algorithm. By constructing the mathematical model for the reactive power voltage control of a photovoltaic power station, learning is optimised continuously in the process of teaching and learning. According to real-time data, the optimal cooperation strategy between the RPVC/AVC control system and intelligent power grid command is formed, and real-time, adaptive and dynamic control of the system is realised. A simulation study is made in this paper, and the simulation results show that the proposed method is reasonable and effective for the 220 kV substation and its feeder system.